Spatial suitability evaluation based on multisource data and random forest algorithm: a case study of Yulin, China - Li, Anqi; Zhang, Zhenkai; Hong, Zenglin; Liu, Lingyi; Liu, Lei; Ashraf, Tariq; Liu, Yuanmin (Frontiers in Environmental Science, 2024)
With a large population and rapid urbanization, there are still many challenges to optimize the ecological-agricultural-urban space. Here, taking Yulin City, situated on the Loess Plateau of China as a case in point, we explored the spatial suitability evaluation of ecological-agricultural-urban space. Building upon the Chinese government's concept of "resource and environmental carrying capacity and territorial development suitability evaluation" (hereinafter referred to as "double evaluation"), this study applies machine learning to the planning of ecological-agricultural-urban space. It explores an intelligent evaluation method for land space patterns using multi-source data. Based on the random forest (RF) algorithm and geographic information system (GIS), resulting in evaluated spatial patterns for ecological-agricultural-urban in the Yulin area. The results showed the constructed random forest models achieved an accuracy of 93% for ecology, 90% for agriculture, and 92% for urban space in Yulin City on the test dataset. By means of suitability analysis, the results indicated that the extremely important ecological space were predominantly located in the southwestern and eastern regions of the study area, while suitable space for agricultural production were primarily scattered throughout the southeast. In contrast, suitable space for urban construction were concentrated mainly in the central part of the study area. The use of machine learning has proven to be